Bowing before Dual Gods: How Structured Flexibility Sustains Organizational Hybridity - Smith, Wendy K.; Besharov, Marya L. (Administrative Science Quarterly, 2019)
Organizations increasingly grapple with hybridity—the combination of identities, forms, logics, or other core elements that would conventionally not go together. Drawing on in-depth longitudinal data from the first ten years of a successful social enterprise—Digital Divide Data, founded in Cambodia—we induce an empirically grounded model of sustaining hybridity over time through structured flexibility: the interaction of stable organizational features and adaptive enactment processes. We identify two stable features—paradoxical frames, involving leaders’ cognitive understandings of the two sides of a hybrid as both contradictory and interdependent, and guardrails, consisting of formal structures, leadership expertise, and stakeholder relationships associated with each side—that together facilitate ongoing adaptation in the meanings and practices of dual elements, sustaining both elements over time. Our structured flexibility model reorients research away from focusing on either stable or adaptive approaches to sustaining hybridity toward understanding their interaction, with implications for scholarship on hybridity, duality, and adaptation more broadly.